Advanced nanocellulose-based gas barrier materials: Present status and prospects. (January 2022) - Wu, Yingji; Liang, Yunyi; Mei, Changtong; Cai, Liping; Nadda, Ashok; Le, Quyet Van; Peng, Yucheng; Lam, Su Shiung; Sonne, Christian; Xia, Changlei
Abstract: Nanocellulose based gas barrier materials have become an increasingly important subject, since it is a widespread environmentally friendly natural polymer. Previous studies have shown that super-high gas barrier can be achieved with pure and hierarchical nanocellulose films fabricated through simple suspension or layer-by-layer technique either by itself or incorporating with other polymers or nanoparticles. Improved gas barrier properties were observed for nanocellulose-reinforced composites, where nanocellulose partially impermeable nanoparticles decreased gas permeability effectively. However, for nanocellulose-based materials, the higher gas barrier performance is jeopardized by water absorption and shape deformation under high humidity conditions which is a challenge for maintaining properties in material applications. Thus, numerous investigations have been done to solve the problem of water absorption in nanocellulose-based materials. In this literature review, gas barrier properties of pure, layer-by-layer and composite nanocellulose films are investigated. The possible theoretical gas barrier mechanisms are described, and the prospects for nanocellulose-based materials are discussed. Graphical abstract: Image 1 Highlights: Gas barriers of pure, layer-by-layer and composite nanocellulose films are reviewed. Gas barrier mechanism of varies nanocellulose films are discussed and compared. Layer by layer nanocellulose composite films exhibit high gas barrier performance. To address drawbacks of nanocellulose, compensation approaches are analyzed. Environmental-friendly advantages of nanocellulose-based materials are discussed.